2017
DOI: 10.3390/w9100785
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Water Usage Efficiency? Characterization of Family Farms in A Semi-Arid Area

Abstract: Water scarcity in Spain is partly due to poor management of this resource in the agricultural sector. The main aim of this study is to present the major factors related to water usage efficiency in farming. It focuses on the Almería coast, southeast Spain, which is one of the most arid areas of the country, and in particular, on family farms as the main direct managers of water use in this zone. Many of these farms are among the most water efficient in Spanish agriculture but this efficiency is not generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Women cooperativists have begun to organize in the last years, with an eye on board seats, but also with a view to cleave closer to sustainable models. In a study on improving water use in Almeria farms, women were found to be more innovative [40]. The cooperative business model has been fundamental in finding more sustainable solutions, where many sustainable farming practices are more knowledge based than product based.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women cooperativists have begun to organize in the last years, with an eye on board seats, but also with a view to cleave closer to sustainable models. In a study on improving water use in Almeria farms, women were found to be more innovative [40]. The cooperative business model has been fundamental in finding more sustainable solutions, where many sustainable farming practices are more knowledge based than product based.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on marketing, logistics, and perishable supply chains have been carried out [36,37]. More recently, there has been an emphasis on transitioning to a more sustainable productive system [38][39][40].…”
Section: Almeria Case Study Justificationmentioning
confidence: 99%
“…Three statistical techniques were used: descriptive analysis, cluster analysis, and the chi-squared test [25,106,107]. Descriptive analysis provided a better understanding of the profile of companies in the sector.…”
Section: Estimation Methodsmentioning
confidence: 99%
“…Worldwide, climate change has meant that recurrent, severe, and widespread droughts will become a common phenomenon in the future [1,2], with adverse implications on water supply [3]. In drought-prone areas, persistent droughts can intersect with other drivers of water scarcity, such as population growth, unsustainable consumption and poor management of water, and legacies of inequality and uneven social vulnerabilities, which collectively result in adverse impacts on different sectors including agriculture, energy, and health [3][4][5][6]. Meanwhile, projections show climate change will likely increase the frequency and severity of droughts globally, particularly in semi-arid regions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, apart from sheer increases in urban population and the associated rising water demand, future gains from technical-oriented solutions can be eroded if wasteful water use practices are not adequately addressed. Therefore, strategies for responding to drought impacts on water scarcity require a combination of both technical and behavioural responses and lie in understanding people's perceptions and water use practices [4,10,13]. According to Olagunju et al [14], "awareness of sustainable water use and the subsequent design of appropriate water policies to promote sound water resources management have become key elements of water debates, both in theory and practice, in recent years".…”
Section: Introductionmentioning
confidence: 99%